Integral valorisation of waste orange peel using combustion, biomethanisation and co-composting technologies. (July 2016) - Siles, J.A.; Vargas, F.; Gutiérrez, M.C.; Chica, A.F.; Martín, M.A.
Highlights: Dried orange peel is a renewable energy resource that can be burnt to generate heat. But high concentration of NO x (4553 mg NO2 /m 3 STP ) is contained in the combustion gases. Biomethanisation of orange peel allows obtaining 29.2 ± 1.5 LSTP  CH4 /kg pre-treated WOP. Co-composting peels (<51% wt.) and organic fraction of municipal waste is suitable. Co-composting peels (at 17% wt.) with municipal waste reduced odour generation by 37%. Abstract: Although recent research has demonstrated that waste orange peel (WOP) is a potentially valuable resource that can be transformed into high value products, heat generation, biomethanisation and composting might be considered the most feasible alternatives in terms of yield. This study revealed that WOP can be successfully valorised through combustion. However, a previous drying step, which generates hazardous wastewater, is required and harmful NO x are emitted with the flue gases. In contrast, a high yield of renewable methane (280 LSTP CH4 /kg added COD, chemical oxygen demand) and an organic amendment can be obtained through the thermophilic biomethanisation of WOP following the removal of valuable essential oils from the peel. Co-composting of WOP combined at different proportions (17–83%) with the organic fraction of municipal solid waste (OFMSW) was also demonstrated to be suitable. Moreover, a 37% reduction in odour generation was observed in co-composting of WOP compared to single composting of OFMSW.